Bodleian Library quarto catalogues I: Greek manuscripts - Coxe, HO (Bodleian Library, 1969)
Coxe's Catalogue of the Greek manuscripts in the Bodleian Library was issued in a small number of copies, and deserves wider circulation. In making this reprint we have added the corrections which have been accumulated. The task of collating and editing them has been undertaken by Miss Ruth Barbour and Mr. Nigel Wilson. The latter has kindly written them in. The opportunity has also been taken to add Coxe's descriptions of the Greek manuscripts in the Canonici collections taken from vol. III of the Quarto Catalogues. They were already included in the index of the present volume. It has not been possible to include the catalogues of the D'Orville and E. D. Clarke collections, which are also indexed here, owing to the different format of the catalogues, but the reader is referred to the now easily accessible descriptions in Summary Catalogue of Western Manuscripts in the Bodleian Library, vol. IV, pp. 37-150,297-311.